MEMBANGUN JARINGAN SOSIAL DALAM PENERAPAN DAKWAH DI TENGAH MASYARAKAT - Abdul Asis Ibrahim; Dewi Asri Ulandari (UIN Mataram, 2020)
Da'wah is an activity that functions as an appeal, invitation, to mankind to return to the right and good path according to religious teachings, and the religion that is blessed by Allah SWT is Islam, this is the basis that Islam is a religion of